PENINGKATAN PENGETAHUAN DAN PARTISIPASI GURU MADRASAH DALAM PELESTARIAN LINGKUNGAN MELALUI WORKSHOP PENGOLAHAN LIMBAH ORGANIK - Siti Zahra Mulianti Natsir; Erma Suryani Sahabuddin; Andi Makkasau; Sitti Hajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Environmental education in madrasahs has great potential to promote environmental conservation through organic waste management. This study aims to analyze the effectiveness of an organic waste processing workshop in improving madrasah teachers’ knowledge and active participation in environmental preservation. A mixed-methods approach was employed, using a one-group pretest–posttest design to measure knowledge improvement, and interviews to explore teachers’ active participation. Quantitative data indicated a significant increase in teachers’ knowledge scores (t(24) = −7001.54; p < 0.001). Qualitative findings revealed that teachers’ active participation in environmental initiatives increased from 65% before the workshop to 90% after, with teachers initiating organic waste management activities within their madrasah environments. These findings demonstrate that a practice-based organic waste processing workshop is effective not only in enhancing teachers’ environmental literacy but also in fostering concrete environmental actions in schools. Practical implications include recommendations for integrating organic waste management programs into teacher professional development and strengthening madrasah policies to ensure program sustainability.